2020
DOI: 10.1101/2020.05.10.086611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Removal of repressive histone marks creates epigenetic memory of recurring heat inArabidopsis

Abstract: 1 Acclimation to high temperature increases plants' tolerance of subsequent 2 lethal high temperatures 1-3 . Although epigenetic regulation of plant gene 3 expression is well studied, how plants maintain a memory of environmental 4 changes over time remains unclear. Here, we show that JUMONJI (JMJ) 5 proteins 4-8 , demethylases involved in histone H3 lysine 27 trimethylation 6 (H3K27me3), are necessary for Arabidopsis thaliana heat acclimation. 7 Acclimation induces sustained H3K27me3 demethylation at key HEAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…To test if JMJ30 and JMJ32 upregulate BZR1 in response to ABA through histone demethylation, we first measured the H3K27me3 levels in the BZR1 locus. In a published genome-wide ChIP-seq dataset, the gene body of the BZR1 was covered with H3K27me3 repressive marks in the absence of hormones, in both wild type and jmj30 jmj32 ref6 elf6 mutants ( Figure 3D ; Yamaguchi et al, 2020 ). H3 levels were also similar in these samples ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test if JMJ30 and JMJ32 upregulate BZR1 in response to ABA through histone demethylation, we first measured the H3K27me3 levels in the BZR1 locus. In a published genome-wide ChIP-seq dataset, the gene body of the BZR1 was covered with H3K27me3 repressive marks in the absence of hormones, in both wild type and jmj30 jmj32 ref6 elf6 mutants ( Figure 3D ; Yamaguchi et al, 2020 ). H3 levels were also similar in these samples ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, JMJ30 and JMJ32 control the ABA and BR signal transduction pathways by regulating distinct downstream targets to balance growth and stress responses through H3K27me3 removal ( Figure 7 ). Overall, H3K27 demethylases tend to have redundant roles during plant development and stress responses ( Lu et al, 2011 ; Gan et al, 2014 ; Zheng et al, 2019 ; Yamaguchi et al, 2020 ). Unlike JMJ30 and JMJ32, ELF6, and REF6 could also control H3K9me3 in a direct way by unknown mechanisms ( Yu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…All Arabidopsis thaliana lines used in this study were in the Columbia (Col-0) background. The jmj30-2 jmj32-1 elf6-1 ref6-3 quadruple mutant was described previously [19]. Prior to growth, genotypes were confirmed by PCR using Emerald Amp polymerase (Takara, Japan) (Figure S1).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Five Arabidopsis Jumonji C domain-containing proteins (JMJs), JMJ30, JMJ32, early flowering (ELF), relative of elf (REF6), and JMJ13, are reported to have H3K27 demethylase activity [12][13][14][15][16][17][18]. We recently reported that JMJ30, JMJ32, REF6, and ELF6 are redundantly required for heat acclimation [19]. After exposure to moderate temperature, JMJs affect the expression of several HSP genes, including HSP21 [20], and remove H3K27me3 at the HSP22 and HSP17.6C loci [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the circadian cycle, Arabidopsis JMJ30 also influences several developmental processes. For example, JMJ30 promotes callus formation from leaf explants ( Lee et al., 2018 ), contributes to abscisic acid-dependent growth arrest ( Wu et al., 2019 ), and has been recently found important for plant heat acclimation ( Yamaguchi et al., 2020 ). This chromatin factor is especially relevant in regulating flowering time.…”
Section: The Jmjc Domain-only Groupmentioning
confidence: 99%